Pengaruh Kualitas Pelayanan , Citra Merek, Dan Kepuasan Pelanggan Terhadap Keputusan Pembelian (Studi Kasus Produk Skincare Cantika Pada Klinik Kecantikan Cantika Kota Metro) - Ratih Mega Susanti; Slamet Tedy Siswoyo; Ana Septiani (Universitas Muhammadiyah Metro, 2025)
Competition between the personal care and cosmetics industry markets is increasinglycompetitive. This is proven by the many types of cosmetics in circulation, both domestic andforeign production. The flood of cosmetic products on the market influences a person'sattitude towards purchasing decisions and using goods. Purchasing a product is no longer tofulfill a need, but rather because of a desire. This research aims to find out whether there isan influence of Service Quality, Brand Image, and customer satisfaction on PurchasingDecisions. This method uses quantitative research. The population in this research arecustomers who subscribe to or have purchased products from the Beauty Clinic. In this study,non-probability sampling was used using a purposive sampling method. The number ofsamples that met the requirements for this study was 64 samples. The data collectiontechnique used was using interviews and questionnaires. Data analysis used includes validitytest, reliability test, normality test, linearity test, homogeneity test and multiple linearregression analysis with the help of the SPSS version 25.0 application. Service quality andcustomer satisfaction have a positive and significant influence on purchasing decisions at theCantika Beauty Clinic in Metro City. Meanwhile, Brand Image does not have a positive andsignificant effect on Purchasing Decisions at the Cantika Beauty Clinic in Metro City